Taking Advantage of a Window of Opportunity : The Rwanda Electronic Single Window for Trade Efficiency - Odhiambo, Alban; Kamajugo, Richard; Zizane, Jackie (International Finance Corporation, Washington, DC, 2017)
Rwanda’s government and private sector took a bold step towards achieving a critical reform agenda with the design and implementationof a single window for international trade system. This implementation marked the first successful collaboration among Rwanda’s numerous agencies that over see the country’s cross-border trade. Addressing the demands of a diverse group of stakeholders was certainly daunting, but effective stakeholder engagement and change management efforts have produced results that are exerting a major impact on the efficiency of goods into and transiting Rwanda. Driving the Single Window project was an aspiration for greater collaboration at the level of government-to-government, business-to business and government-to-business. Rwanda’s membership in the East African Community, which is a Single Customs Territory was another critical factor. By addressing national needs and incorporating a regional focus and outreach in the management of cargo, the Rwanda Electronic Single Window has achieved success.